Ways of Effective Organization of Investment Processes in The Industry Network and the Importance of State Programs - Kasimov Azamat Abdukarimovich (European Science Publishing, 2024)
In this article, the essence of the state policy on the effective use of the inputs introduced into the industrial network, and the main goals aimed at it are highlighted. Factors affecting investment attractiveness in industrial network enterprises and investment attractiveness evaluation directions were analyzed. Also, the main dynamics of increasing investment trends in this industry are shown.
Keywords: investment, investment attractiveness, state investment policy, source of investment, industrial enterprise.